2021
DOI: 10.3390/cancers13164058
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Architecture Influences the Biological Effectiveness of Boron Neutron Capture Therapy in In Vitro/In Silico Three-Dimensional Self-Assembly Cell Models of Pancreatic Cancers

Abstract: Pancreatic cancer is a leading cause of cancer death, and boron neutron capture therapy (BNCT) is one of the promising radiotherapy techniques for patients with pancreatic cancer. In this study, we evaluated the biological effectiveness of BNCT at multicellular levels using in vitro and in silico models. To recapture the phenotypic characteristic of pancreatic tumors, we developed a cell self-assembly approach with human pancreatic cancer cells Panc-1 and BxPC-3 cocultured with MRC-5 fibroblasts. On substrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…This total culture time differed to the 37-day total scaffold culture time frame described here. Similar to Görte et al (2020), Yu et al (2021) investigated new modalities for PDAC, describing PANC-1 and BxPC-3 spheroids co-cultured with fibroblasts for the investigation of boron neutron capture therapy (1.2 MW for 28 min) [ 54 ]. This research reported lower survival rates and higher apoptosis rates in 3D spheroids compared to 2D cultures after thermal neutron irradiation treatment [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This total culture time differed to the 37-day total scaffold culture time frame described here. Similar to Görte et al (2020), Yu et al (2021) investigated new modalities for PDAC, describing PANC-1 and BxPC-3 spheroids co-cultured with fibroblasts for the investigation of boron neutron capture therapy (1.2 MW for 28 min) [ 54 ]. This research reported lower survival rates and higher apoptosis rates in 3D spheroids compared to 2D cultures after thermal neutron irradiation treatment [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Hehlgans et al (2009) identified Caveolin-1 and TAE226 as potential radiosensitisers (in radiotherapy doses of 0–6 Gy) for the pancreatic cancer cell line MiaPacCa2 in a spheroid system [ 51 , 52 ]. Moreover, PDAC spheroids are emerging as platforms to test new modalities such as proton therapy and boron neutron capture therapy [ 53 , 54 ]. Overall, spheroid models can be considered an advanced platform supporting more realistic 3D cellular interactions compared to traditional 2D cell cultures for radiation response studies, however, these models lack robust porosity, ECM controlled composition, and mechanical stability [ 25 , 27 , 28 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the three-dimensional structure of the tumor and its resistance to therapy is being actively studied [ 49 , 50 , 51 ]. We have tested the proposed fluorescence-based approach to analyze the peculiar features of the cellular response to the action of cytotoxic low- and high-molecular agents during cell growth in a collagen hydrogel.…”
Section: Discussionmentioning
confidence: 99%
“…25 In a previous study, the 3D structures of tumor spheroids not only influenced the BPA uptake of pancreatic cancer cells but also altered such cells’ BNCT responses. 26 When a microfluidic chip was used in conjunction with large-area microscopy, the radiation biological responses of more than 40 spheroids could be monitored simultaneously using that one chip. Tumor spheroids with two diameters were used herein to evaluate the influence of hypoxia on the efficacy of BNCT.…”
Section: Introductionmentioning
confidence: 99%